Food handlers : manual, Instructor - Carvalho, Douglas Rosa de (Food and Agriculture Organization of the United Nations, 2017)
[Introduction]. Food-borne diseases (FBDs) are one of the most frequent public health problems in daily life. The hazards that cause FBD may occur in the different stages of the food chain (from primary production to the table). Independently from its origin, once the food reaches the consumer it may have an impact on public health and cause severe economic damage to the establishments devoted to its preparation and sale. These two events may cause loss of confidence and the closing down of a business. Fortunately, the measures for preventing food contamination are very simple and may be applied by anyone who handles food, by following easy rules for hygienic food handling. This Manual’s purpose is to provide to people who handle food, and particularly to food-handlers’ instructors, the information they need to facilitate the teaching of proper procedures to food workers. In addition, it seeks to provide basic information about food safety that Latin American and Caribbean countries may adapt to their own needs. The Manual is organized into three Modules and Appendixes focusing on the following topics: (1) food hazards; (2) FBDs; and (3) hygienic measures to prevent food contamination. The evaluation at the end, forms part of the Manual. Its purpose is to assess the knowledge learned during the course regarding the importance of hygienic food handling for public health.
Keywords: manipulace s potravinami; Foodborne Diseases; Hygiene; nemoci přenášené potravou; hygiena; zemědělství a potravinářství; Food Contamination; kontaminace potravin; bezpečnost potravin; Food Safety; Food Handling